Hygro-thermo-mechanical analysis of brick masonry walls subjected to environmental actions - Ramirez Alvarez de Lara, Rafael (2023)
Masonry walls comprise an important part of the building envelope and, thus, are exposed to environmental effects such as temperature and moisture variations. However, structural assessment usually neglects the influence of these hygro-thermal loads and assumes ideal conditions. This paper presents a hygro-thermo-mechanical model and its application to simulate the impact of temperature- and moisture-related phenomena on the structural behavior of masonry walls. A fully coupled heat and mass transfer model is presented and a 2D finite element model is prepared to simulate the behavior of a brick masonry wall under various hygro-thermal scenarios. Two different mortars are considered: namely, cement mortar and natural hydraulic lime mortar. The results are evaluated in terms of temperature and moisture content distribution across the wall thickness. The hygro-thermal model is further extended to incorporate mechanical effects through the total strain additive decomposition principle. It is shown that the hygro-thermo-mechanical response of the brick masonry wall is a complex 2D phenomenon. Moreover, the environmental loads change the natural stress distribution caused by gravitational loads alone. Finally, the wall with cement mortar develops higher levels of stress when compared to the one with lime mortar, due to the dissimilar hygro-thermal behavior between the constituent materials.